Encyclopedia of heavy metal music - Phillips, William, 1961- (Greenwood, 2009)
Providing an extensive overview of the music, fashion, films, and philosophies behind the movement, this encyclopedia chronicles the history and development of heavy metal, including sub-movements such as death metal, speed metal, grindcore, and hair metal.